The Disraeli Family and the history of the Jews - Goodman, M (Oxford Centre for Hebrew and Jewish Studies, 2020)
One of the illustrated Victorian editions of Whiston’s translation of Josephus, printed in London in 1848, contains ‘a Sequel to the History of the Jews; continued to the present time’. The title page gives no indication of the origins of this Sequel, which comprises a substantial history of the Jews from the first century CE to the nineteenth century. The article discusses the reasons to suppose that the Sequel was composed by the literary historian Isaac D’Israeli and completed rapidly after his death by his children, Benjamin Disraeli and his sister Sarah. The composition and publication history of the Sequel shed light both on the Jewish identity of Isaac and on the complex attitude of Benjamin to the public debates on Jewish emancipation, in which he intervened dramatically for the first time in December 1847.